Determination of Fluoride in Drinking Water and Black Tea by Ion Selective Electrode Using Standard-Addition Method - Karami Nogourani, Maryam; Talebi, S.M.; Ebrahimian, M. (Asian Journal of Chemistry, 2012)
The fluoride content of drinking water and popular black tea in Iran was determined by ion selective electrode and standard addition method. A recovery test indicated that the method is quite reliable to determine the trace fluoride in sample solutions. The concentration of fluoride in drinking water in different mega cities was in the range of 0.12-0.31 μg/L. The concentration of fluoride in popular black tea extracts was in the range of 2.54-3.73 but the fluoride content in tea extract is depended to the infusion time.